Strong pathogen competition in neonatal gut colonisation - Tommi Mäklin; Harry A. Thorpe; Anna K. Pöntinen; Rebecca A. Gladstone; Yan Shao; Maiju Pesonen; Alan McNally; Pål J. Johnsen; Ørjan Samuelsen; Trevor D. Lawley; Antti Honkela; Jukka Corander (Nature Communications, 2022)
Opportunistic bacterial pathogen species frequently colonise the human gut as a normal part of the ecosystem but strain-level colonisation and competition dynamics in healthy hosts is yet to be established. Authors seek to understand the relationship between colonisation potential and ecological factors modulating pathogen prevalence in disease in a longitudinal cohort.